Efecto de la concentración de glifosato presente en cuerpos de agua cercanos a campos de soya transgénica sobre la abeja Apis mellifera y la abeja sin aguijón Tetragonisca angustula - Ruiz-Toledo, Jovani; Sánchez-Guillén, Daniel (Instituto de Ecología, A.C., 2014)
We evaluated the toxicity of field concentrations of glyphosate on the mortality of two bee species occurring in the Soconusco Region, Chiapas, Mexico. We did not find any significant difference in the mortality between exposed and control groups